Sistema Web Integrado de Citologías (SICI) - Rivas Hernández, Christopher Andrés (2010)
Rivas Hernández, C. A . & Adolio Cascante, J. A. (2010). Sistema Web Integrado de Citologías (SICI). [Tesis de Licenciatura]. Heredia, C.R.